Medgar Evers : Mississippi Martyr - Williams, Michael Vinson, 1971- (Book collections on Project MUSE., 2011)
Civil rights activist Medgar Wiley Evers was well aware of the dangers he would face when he challenged the status quo in Mississippi in the 1950s and '60s, a place and time known for the brutal murders of those who challenged the status quo. Nonetheless, Evers consistently investigated the rapes, murders, beatings, and lynchings of black Mississippians and reported them to a national audience, all the while organizing economic boycotts, sit-ins, and street protests in Jackson as the NAACP's first full-time Mississippi field secretary. He organized and participated in voting drives and nonviolent direct-action protests, joined lawsuits to overturn school segregation, and devoted himself to a career that cost him his life. This biography of a lesser-known but seminal civil rights leader draws on personal interviews from Evers's widow, his remaining siblings, friends, schoolmates, and fellow activists to elucidate Evers as an individual, leader, husband, brother, and father. His story is a testament to the important role that grassroots activism played in exacting social change.--From publisher description.